La ley de cupo laboral trans como medida positiva contra la desigualdad estructural: logros y desafíos - González, Agostina Daniela (2017)
This paper proposes an analysis of the Buenos Aires Trans Worker Quota Law as a positive measure against structural inequality suffered by a group of people that are not able to exercise their right to work. Thus, this law is considered as a fundamental measure but the importance of incorporating public structural policies rather than unidimensional ones is highlighted. In order to achieve the incorporation of public structural policies, life conditions of trans population and the Argentine regulatory framework of gender identity are approached. Then, arguments that assist and justify the adoption of positive measures destined to eliminate structural inequality are mentioned.